Competing Paradigms in Industrial Relations - Adams, Roy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
Despite the statute which the field of industrial relations has achieved, many essential issues regarding its nature and purpose continue to be controversial. There has emerged no universally accepted definition of the term industrial relations. The author at-tempts to demonstrate that the failure is the result of underlying conceptual structure of the field.